INTEGRASI CORPORATE GOVERNANCE DAN ETIKA BISNIS SEBAGAI FONDASI KEBERLANJUTAN PERUSAHAAN - Indrastuti, Dewi Kurnia; Ferry Suhardjo; Irwanto Handojo; Arief Effendi, Muhammad; Elvy Napitupulu, Bertha (Jurnal Abdi Masyarakat, 2025)
The failure of governance and business ethics can have detrimental effects on companies and stakeholders. As such, a strong grasp of governance and business ethics is crucial for organizations to achieve sustainable success and to better withstand crises, thus boosting their competitiveness. The Corporate Governance and Business Ethics webinar, part of the Tridharma Perguruan Tinggi initiative for lecturers at Sekolah Tinggi Ilmu Ekonomi Trisakti and Sekolah Tinggi Ilmu Ekonomi Jayakarta, was organized in partnership with KJA Surya Dinamika Global Makmur. Its goal was to provide participants with a thorough understanding of corporate governance and business ethics concepts, along with practical insights based on the latest regulations. Held on June 19th, 2025, the three-hour session attracted 205 participants from both domestic and international backgrounds. Out of 97 respondents who completed an evaluation form, 95% praised the speakers' quality, 89.7% found the content relevant, and 84,5% considered the webinar highly beneficial.